2018
DOI: 10.1371/journal.pone.0198505
|View full text |Cite
|
Sign up to set email alerts
|

Optimal age of the donor graft tissue in relation to cultured pearl phenotypes in the mollusc, Pinctada margaritifera

Abstract: Ageing is defined as the progressive decline in tissue and organ functions over time. This study aims to evaluate the ageing effect on cultured pearl quality phenotypes (including size and quality traits) in the graft-recipient animal model: Pinctada margaritifera. For this, eight uniform grafting experiments were designed using two hatchery-produced pearl oyster families as donors, which were followed through time, between 7 and 30 months in age. For each age category, 20 donors were studied for each culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…RT-qPCR was used to validate the expression patterns in the pearl sac, observed in RNA-seq, for key genes commonly used as markers of pearl quality traits, namely pif-177 , aspein, shematrin-9 and the mantle protein 10 (MP10). DNAse tratment of total RNA, cDNA sunthesis and amplification procedure has been publised previously [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-qPCR was used to validate the expression patterns in the pearl sac, observed in RNA-seq, for key genes commonly used as markers of pearl quality traits, namely pif-177 , aspein, shematrin-9 and the mantle protein 10 (MP10). DNAse tratment of total RNA, cDNA sunthesis and amplification procedure has been publised previously [19].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in P. margaritifera , based on controlled bi-parental crosses and the F1 generation, demonstrated heritability ( h 2 from 0.21 to 0.37) for nacre weight and thickness, pigmentation darkness and colour, surface defects and grade, signifying a donor oyster effect with a genetic basis, although there were also important interaction components [10]. Previous studies reported that location, temperature and food availability [1113], pearl rotation [14], donor oyster genotype [4, 9, 1518], age [19], position of graft mantle [20] and contamination during the graft operation and/or graft operator skills [21] are all determinants of final pearl quality and do not necessarily affect similar traits.…”
Section: Introductionmentioning
confidence: 99%
“…Blay et al. () also reported that the age of the donor oyster influenced the pearl size, with results showing that mantle tissues from young donors (12 and 18 months of age) produced the biggest pearls with the highest quality (grade and luster), which was buttressed by the high expression level of biomineralization genes in the younger donors. These findings correspond to the results from the current study, which analyzed biomineralization genes in 1.5‐ and 2.5‐year‐old oysters and recorded significantly higher expression levels of Pearlin * and Nacrein * in the younger oysters.…”
Section: Discussionmentioning
confidence: 97%
“…Pearlin is a matrix protein between aragonites that is involved with the development of the nacre layer by moving Ca² + to the nucleus (Montagnani et al 2011). Donor age has been reported to affect the mRNA expression of aragonite-related genes (Pif-177*, MSI60*, and Pearlin*), calcite-related genes (Aspein*, Shema-trin5*, and Prismalin*), and the gene involved in developing the nacre and prismatic layers (Nacrein*) of the pearl sac (Blay et al 2018). The increase in nacre accumulation equaled 7.2 μm/d within the second year and declined with age, attaining an average value of 3.1 μm/d (Pouvreau et al 2000).…”
Section: Biomineralization Capacitymentioning
confidence: 99%
“…Pearls are biomineralized products of shellfish species like pearl oysters and mussels. Pearl oysters are marine organisms mainly cultivated for pearl production with a vast array of species such as Pinctada margaritifera , Pteria penguin , Pinctada fucata martensii and Pinctada maxima (Blay, Planes, & Ky, 2018; Southgate, Lucas, & Saucedo, 2008). Pearl oyster P. fucata martensii is used to produce pearls with size of 4.5–8.5 mm, while P. maxima and P. margaritifera mostly produce large sized pearls (>10 mm).…”
Section: Introductionmentioning
confidence: 99%